2021
DOI: 10.3390/rs13050969
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Surface NO2 Concentrations over Germany from TROPOMI Satellite Observations Using a Machine Learning Method

Abstract: In this paper, we present the estimation of surface NO2 concentrations over Germany using a machine learning approach. TROPOMI satellite observations of tropospheric NO2 vertical column densities (VCDs) and several meteorological parameters are used to train the neural network model for the prediction of surface NO2 concentrations. The neural network model is validated against ground-based in situ air quality monitoring network measurements and regional chemical transport model (CTM) simulations. Neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 64 publications
2
23
0
2
Order By: Relevance
“…For Romania, which was one of our study regions, [24] reported that annual SO 2 from power plants decreased between 2005 and 2015, while NO 2 emissions were more or less stable during that time period. TROPOMI led to a new area of top-down NO 2 emission monitoring from space [25,26], as well as bringing advances for surface NO 2 concentration estimates (e.g., [27]). For SO 2 , despite the increased sensitivity of TROPOMI, in 2018/2019 only the largest SO 2 emitters in Europe, e.g., the Polish Bełchatów coal power plant, were visible from space, due to the installation of flue gas desulfurization systems in the European Union [28].…”
Section: Introductionmentioning
confidence: 99%
“…For Romania, which was one of our study regions, [24] reported that annual SO 2 from power plants decreased between 2005 and 2015, while NO 2 emissions were more or less stable during that time period. TROPOMI led to a new area of top-down NO 2 emission monitoring from space [25,26], as well as bringing advances for surface NO 2 concentration estimates (e.g., [27]). For SO 2 , despite the increased sensitivity of TROPOMI, in 2018/2019 only the largest SO 2 emitters in Europe, e.g., the Polish Bełchatów coal power plant, were visible from space, due to the installation of flue gas desulfurization systems in the European Union [28].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study nonetheless indicate that the TROPOMI NO 2 dataset provides sufficiently high data availability and thus very valuable spatiotemporal information on NO 2 pollution for urban areas in Norway during spring, summer, and fall. During these periods, the TROPOMI NO 2 data have significant potential even in a challenging environment such as Norway for, e.g., local-scale NO 2 mapping and monitoring, including applications relevant for human exposure such as surface-level NO 2 mapping, which converts the column-based retrievals from TROPOMI or similar satellite instruments to surface NO 2 concentrations based on additional information obtained from either chemistry transport models [18] or statistical relationships between satellite-based column information and surface monitoring stations [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML) is gaining traction as an alternative modeling tool to complement CTM in Earth system science fields [20][21][22][23][24][25][26] . Because photo-chemical processes have a significant impact on ozone, ML models are trained using a wide range of meteorological variables, many of which drive photo-chemical processes [27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%